Analisis Perancangan Sistem Informasi Pencatatan Anggaran dan Realisasi Pengeluaran ATK Pada Kantor Urusan Agama Kecamatan Sosa - Sari, Hamidah; Daulay, Aqwa Naser (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine the information system for recording budgets and the realization of ATK expenditure that is currently running at the Sosa District Religious Affairs Office (KUA), and to develop a computerized information system for recording budgets and realization of ATK expenditure at this office. This study used descriptive qualitative method. Data collection techniques in this research used interview techniques, observation and literature study. The author designed a system using the Microsoft Visual Studio 2010 programming language and mySQL database to overcome existing problems, and this can only be used at the Sosa District Religious Affairs Office in processing Office Stationery (ATK) data. The information system design methods used by the author are DFD, ERD, Normalization, and RAT to produce ATK reports that are more effective and efficient. The results of the research show that the design of the budget recording system and the realization of ATK expenditure at the Sosa District Religious Affairs Office (KUA) includes an entry plan and an exit plan, the entry plan starts from the login form, main menu, budget form, goods form, employee form, payment form . Meanwhile, the exit design is only a draft report produced by the system being designed.